Răspuns :
1. 3x - 1 ,(3) = 1 ,(5)
3x = 1,(5) + 1 .(3) = 14 /9 +12 /9 = 26 /9
x = 26 / 9 ·3 = 26 / 27
2. - x - 1 /2 = 2²
- x = 4 +1 /2
- x = 9 /2
x = - 9 /2
3. x + 1 ,2 = - 2x
x + 2x = - 1 ,2
3x = - 1 ,2
x = - 1 ,2 : 3 = - 0,4
4. x + 3 / 5 = - 2x
x + 2x = - 3 / 5
3x = - 3 / 5 ; x = - 3 / 3 ·5 = - 1 / 5
5. x / 4 = 2x - 1,5
x = 8x - 4· 1,5 ; x = 8x - 6 ; x - 8x = - 6
- 7x = - 6 ; x = 6 / 7
6. x + y = 11,2
x = 1,4 +y ⇒ 1,4 +y +y = 11,2 ⇒ 2y =11,2 -1,4
2y = 9,8 ; y = 9,8 :2 = 4,9 si x = 1,4 + 4,9 = 6,3
7. x - y =21 /5
x = 2y / 5 ⇒ 2y /5 - y =21 / 5
2y - 5y =21
- 3y =21 ⇒ y = - 7
x = 2 · ( -7) / 5 = - 14 / 5
3x = 1,(5) + 1 .(3) = 14 /9 +12 /9 = 26 /9
x = 26 / 9 ·3 = 26 / 27
2. - x - 1 /2 = 2²
- x = 4 +1 /2
- x = 9 /2
x = - 9 /2
3. x + 1 ,2 = - 2x
x + 2x = - 1 ,2
3x = - 1 ,2
x = - 1 ,2 : 3 = - 0,4
4. x + 3 / 5 = - 2x
x + 2x = - 3 / 5
3x = - 3 / 5 ; x = - 3 / 3 ·5 = - 1 / 5
5. x / 4 = 2x - 1,5
x = 8x - 4· 1,5 ; x = 8x - 6 ; x - 8x = - 6
- 7x = - 6 ; x = 6 / 7
6. x + y = 11,2
x = 1,4 +y ⇒ 1,4 +y +y = 11,2 ⇒ 2y =11,2 -1,4
2y = 9,8 ; y = 9,8 :2 = 4,9 si x = 1,4 + 4,9 = 6,3
7. x - y =21 /5
x = 2y / 5 ⇒ 2y /5 - y =21 / 5
2y - 5y =21
- 3y =21 ⇒ y = - 7
x = 2 · ( -7) / 5 = - 14 / 5